EpiDoC Unit - a clinical research unit open to the rheumatology community - Canhão, Helena (2021)
EpiDoC is an epidemiology and outcomes research unit, with a main focus in Rheumatology clinical research but also in other non-communicable chronic diseases. Established in 2016, it is located at NOVA Medical School1 – CEDOC, and integrates the Comprehensive Health Research Center (CHRC)2, a clinical and public health research unit, scored Excellent by Fundação Ciencia e Tecnologia (FCT) 2019’s evaluation.